Forced eLearning Acceptance using TPB: High School vs University Students - Sarosa, Samiaji (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
Covid 19 Pandemic has forced Indonesian students to utilize eLearning tools. This article tests the acceptance of forced eLearning by Indonesian high school and students using Theory of Planned Behavior. The study extended original TPB to include Perceived Cost, Perceived Risks, Trust (both organization and application), Perceived Ease of Used, Perceived Usefulness, Controllability, and Self-efficacy. We also conducted Multi Group Analysis to see if university students and high school students have differences in their acceptance.